Economic and cyber security: Collective monograph - Victor Krasnobayev; Alina Yanko; Alina Hlushko; Oleg Kruk; Oleksandr Kruk; Vitalii Gakh; Svitlana Onyshchenko; Oleksandra Maslii; Oleksandr Kivshyk; Kateryna Potapova; Mykola Nalyvaichuk; Vasyl Meliukh; et al. (PC TECHNOLOGY CENTER, 2023)
Collective monograph highlights the results of systematic scientific research devoted to the problems of economic cyber security as a component of the financial security of the state, and contains practical recommendations on measures to strengthen the security of the state, in particular strategically important enterprises, in the presence of modern threats. Chapter 1 analyzes the position of Ukraine in the global cyber security ratings and outlines promising directions for increasing its level, one of which is the improvement of information protection systems of critical infrastructure objects. A data comparison algorithm is considered, which consists in continuous monitoring and scanning of data by constantly comparing data with information patterns of users and services, as well as threat patterns and indicators based on previous experience, not only one's own, within a local network or system, but also globally scale An improved method of rapid data comparison is presented, which provides maximum accuracy of comparison with a minimum amount of equipment for comparing devices. Its use makes it possible to identify potential cyber threats and take preventive measures, which will increase the level of protection of critical infrastructure objects. Chapter 2 focuses on defining strategic directions for ensuring economic cyber security of business in Ukraine. The importance of information protection in the context of the development of the digital economy has been updated, and the place of economic cyber security in the national security system has been determined. A thorough analysis of the dynamics of cyber incidents in the world in recent years was carried out and the specifics of the manifestation of cyber threats at the macro and micro levels were outlined. Special attention is paid to the intrusion detection process and a detailed study of the working principles of modern intrusion detection and prevention systems. It is expected that the use of the proposed recommendations on the cyber security policy will significantly increase the level of information security (confidentiality, integrity and availability) of the business. Chapter 3 is dedicated to solving the problem of strengthening the security of strategically important enterprises of Ukraine by developing effective forms of implementation of the state regulatory policy in this direction. The issue of identifying strategically important enterprises and forming their security at the state level as a basis for supporting and restoring the national economy has been updated. The strategic directions of deregulation of business activity in Ukraine, including strategically important enterprises, have been determined. One of them is institutional support of state regulatory policy, improvement of regulatory policy. On the basis of the analysis of the existing institutional support of the state regulatory policy regarding strategically important enterprises, it has been proved that the basis of the formation of effective forms of implementation of the state regulatory policy of support and strengthening of the security of strategically important enterprises is the need to improve the current legislation, the formation of effective institutional and organizational support and the clustering of the national economy based on strategic important enterprises with the possibility of creating integrated corporate structures. A model of the process of assessing the effectiveness of the implementation of the state regulatory policy on ensuring the security of strategically important enterprises is proposed, which provides regulatory bodies with a tool to influence its level with the provision of economic development and social stability in Ukraine. Chapter 4 explores Semantic role labeling (SRL) as a key Natural Language Processing (NLP) task that plays a vital role in extracting meaningful information from text. The role of SRL and its application is considered in the context of economics and cyber security, because the accurate definition and analysis of semantic roles in text is critical due to the rapid increase in the amount and complexity of textual information. State-of-the-art NLP classifiers used in decision-making, market analysis and financial reports, media articles, and economic texts are reviewed. It is emphasized that the process of determining relevant information from a large array of data collected from disparate sources requires an optimal methodological base, which should include the use of special tools for cleaning, tokenization, marking parts of speech with labels for preparation for NLP analysis. With the help of NLP classifiers, it becomes possible to automatically identify data, which allows to get information about market trends or security threats, depending on the specific field. It is noted that the proposed methods are practically significant, as they improve the ability to extract useful information, assess risks and make informed decisions by organizing unstructured textual data. Chapter 5 is dedicated to the comprehensive substantiation of the theoretical and methodological foundations and practical methods of monitoring the state of financial security of Ukraine in conditions of economic turbulence as a factor ensuring the preservation of the state's financial system. Indicators of the state of financial security of regions are proposed and it is proved that they are not strongly connected, and also interconnected with the state of financial security of the state, which allows their use as input information in the process of calculating the integral indicator of the state of financial security of the region. On the basis of the proposed methodology for assessing the state of financial security of regions, integral indicators of the state of financial security of regions of Ukraine were calculated, which are actually the result of collapsing indicators by subsystems into a system index for a certain region, high values of which characterize a relatively stable value of financial security of a certain region, and low values signal its dangerous or critical condition. Chapter 6 discusses the essence and features of the circular economy as an innovative com-ponent of the modern economy, which functions and develops on the basis of sustainable devel-opment, the deep reasons for its emergence, formation and transformation into a factor in the formation of a new paradigm of the global economy. Being a mechanism for the implementation of the Global Goals of sustainable development, the concept of a closed cycle economy encourages highly deve loped countries and businesses to introduce innovations and define the development of a circular economy as a priority in their long-term strategies. The monograph is intended for researchers who are engaged in the development of measures to increase the financial security of the state, primarily through the development or improvement of security systems in cyberspace, as well as practitioners who are looking for the best scientific solutions for implementation, which can contribute to the formation of reliable cyber protection measures in the information environment of the enterprise, contributing to the increase of its financial security. The monograph is also useful for state authorities, which are forced to search for operational, most effective solutions to ensure the financial security of the state as a whole, its strategic enterprises, including critical infrastructure, in particular through the regulation of security measures in the information space, in the presence of modern external threats.
Keywords: 000; Integer economic data processing systems; modular number system; non-positional number system; economic cyber security; national economy; intrusion detection systems; unauthorized access; strategically important enterprises; state regulatory policy; institutional support; semantic role labeling; natural language processing; monitoring financial security; national security; circular economy